Freedom of Speech: Dimensi Kebebasan dalam Paradigma Komunikasi Dakwah - Rasyid, Abdul (Jurnal Ilmu Dakwah, 2008)
The freedom of opinion as freedom of speak constitute one of important factor to build democrazy. The scaientist agree that is no absolute freedom. The freedom always assumed have conditions. As it also with freedom of speak. It occures in law limits is used by state or nation.